Finite element model of iron powder compaction at above room temperature - Rahman M.M.; Ariffin A.K. (American Institute of Physics Inc., 2023)
This paper presents the finite element modelling of iron powder compaction process at above ambient temperature. The deformation behaviour of powder mass at elevated temperature was assumed to be rate independent thermo-elastoplastic material where the material constitutive laws were derived based on a continuum mechanics approach by considering a large displacement based finite element formulation. The temperature dependent material parameters were established through experimentation. Two constitutive relations namely Mohr-Coulomb and Elliptical Cap yield models were used to represent the deformation behaviour of the powder mass during the compaction process. These yield models were tested, however an Elliptical Cap model was shown to be the most appropriate to represent the compaction process. The staggered-incremental-iterative solution strategy was established to solve the non-linearity in the systems of equations. Some numerical simulation results were validated through experimentation, where a good agreement was observed. 2015 AIP Publishing LLC.